Greyboy : finding blackness in a white world - Brown, Cole (Arcade Publshing, 2020)
"Cole has heard it all before--token, bougie, oreo, Blackish--the things we call the kids like him. Black kids who grow up in white spaces, living at an intersection of race and class that many doubt exists. He needed to get far away from the preppy site of his upbringing before he could make sense of it all. Through a series of personal anecdotes and interviews with his peers, Cole transports us to his adolescence and explores what it's like to be young and in search of identity. He digs into the places where, in youth, a greyboy's difference is most acutely felt: parenting, police brutality, Trumpism, depression, and dating, to name a few. 'Greyboy: Finding Blackness in a White World' asks an important question: What is Blackness? It also provides the answer: Much more than you thought, dammit."--Page [2] of cover.